PENGARUH STRATEGI PEMBELAJARAN TEAM QUIZ BERBANTUAN WORDWALL TERHADAP KEMAMPUAN PENALARAN SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V - Nadia Nurul Azmi; Nurjamaludin; Eko Fajar Suryaningrat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematical reasoning abilities of fifth-grade students, particularly in mixed arithmetic operations. The purpose of this study is to determine the effect of the Team Quiz learning strategy assisted by Wordwall on students' mathematical reasoning abilities in mathematics. The method used is a quantitative approach with a quasi-experimental design. The research instrument used was a mathematical reasoning test consisting of 10 description items. Based on the instrument trial conducted on 31 students at SDN 3 Bayongbong, the results showed that 9 out of 10 items were declared valid with a very high reliability coefficient of 0.948. These results indicate that the instrument used is suitable for measuring students' reasoning abilities. The implementation of the Team Quiz strategy assisted by Wordwall media is expected to provide a more active, collaborative, and fun learning experience, thereby stimulating students to improve their mathematical reasoning abilities logically and systematically